Konsep Justice Collabolator dan Kedudukannya sebagai Alat Bukti dalam Peradilan Pidana - Iqbal, Shulhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This paper aims to provide an understanding of the concept of Justice Collabolator as evidence in a trial that provides opportunities for perpetrators of criminal acts to become Justice Collabolators and want to cooperate with law enforcement. The research method used is normative juridical with an analytical descriptive approach, using the Legislation Approach. This research uses the Law Approach by collecting and analyzing statutory provisions related to Justice Collaborators. The legal material collection technique used is library research, then analyzed qualitatively. The results showed that the concept of Justice collaborator is needed to assist law enforcement officials in uncovering criminal cases, but on the other hand, there are still many ineffective because the defendant is afraid to tell the truth in court, based on this, legal regulations are needed that can make it easier for the defendant to tell the truth what has happened, so that the legal objectives of certainty, expediency and legal justice are achieved and for the defendant or convicted.